Cost And Time Analysis Of Changing River Bank Reinforcement Work From Corrugated Concrete Sheet Pile To Multipurpose Panel System - Muhammad Fajar Nugroho; Henny Pratiwi Adi; Slamet Imam Wahyudi (International Journal of Health Engineering and Technology, 2026)
Riverbank reinforcement plays a vital role in maintaining slope stability and protecting nearby infrastructure. However, the commonly used Corrugated Concrete Sheet Pile (CCSP) method often faces challenges such as high costs, long construction duration, and limited availability of precast materials. As an alternative, the Concrete Panel method offers a more efficient and practical solution. This study aims to analyze the comparison of cost and time between the CCSP and Concrete Panel methods in riverbank reinforcement work. This research applies a descriptive quantitative approach by analyzing work volumes and cost data derived from the project’s Bill of Quantity (BoQ) documents. Cost analysis was carried out by comparing the unit rate of each work component, while time analysis was based on the production capacity of each work item and the development of a Gantt Chart to determine the total project duration. The results indicate that the Concrete Panel method can reduce project costs by approximately Rp 1.73 billion or 8.89%, and shorten the construction duration to 102 days, which is 26 days faster or about 20.3% more efficient than the CCSP method. In addition to its cost and time efficiency, the Concrete Panel method provides advantages in installation flexibility and quality control. Therefore, adopting the Concrete Panel method can be considered an effective and sustainable alternative for riverbank reinforcement projects.